2018
DOI: 10.1002/jhet.3214
|View full text |Cite
|
Sign up to set email alerts
|

Design, Synthesis and Computational Studies of Novel Carbazole N‐phenylacetamide Hybrids as Potent Antibacterial, Anti‐inflammatory, and Antioxidant Agents

Abstract: in Wiley Online Library (wileyonlinelibrary.com).The present study deals with the synthesis of N-phenylacetamide-functionalized carbazole derivatives and their antibacterial, anti-inflammatory, and antioxidant assays. In vitro antibacterial studies of synthesized compounds shows prominent activity against Staphylococcus aureus, Bacillus subtilis, Escherichia coli, and Pseudomonas aeruginosa. In addition, in silico molecular docking studies corroborated that the methyl substituent (3g), (3h), and (3i) showed pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…N-phenylacetamide-functionalized carbazole derivatives were synthesized and tested for antibacterial, anti-inflammatory and antioxidant activity. In vitro antibacterial studies have shown promising activity against Staphylococcus aureus, Bacillus subtilis, Escherichia coli and Pseudomonas aeruginosa strains [14].…”
Section: Introductionmentioning
confidence: 99%
“…N-phenylacetamide-functionalized carbazole derivatives were synthesized and tested for antibacterial, anti-inflammatory and antioxidant activity. In vitro antibacterial studies have shown promising activity against Staphylococcus aureus, Bacillus subtilis, Escherichia coli and Pseudomonas aeruginosa strains [14].…”
Section: Introductionmentioning
confidence: 99%
“…A molecular docking study revealed that they were able to bind to receptor 2MBR. Compounds 3g, 3i, and 3h interacted with the active site of the MurB enzyme receptor in E. coli cells, and demonstrated a stronger capability to inhibit this receptor, compared to ciprofloxacin [ 14 ]. Merzouki at al.…”
Section: Discussionmentioning
confidence: 99%
“…Lubricating oils play an important role in the long-term and reliable operation of equipment, implementation of intelligent and green manufacturing, industrial foundations, and other major engineering systems. Various additives are often added to lubricating oil [ 5 , 9 14 ], among which antioxidants are indispensable and must be added to lubricating oils to slow down the rate of oxidation deterioration to prolong the service life of lubricating oil and significantly improve its thermal stability and antioxidant properties. The oxidation of lubricating oil is essentially a hydrocarbon oxidation process, and its mechanism is a free-radical chain reaction.…”
Section: Introductionmentioning
confidence: 99%